General Data Protection Regulation and Horizon 2020 Ethics Review Process: Ethics Compliance under GDPR - Kuyumdzhieva, Albena (Bioethica, 2019)
The present manuscript examines the new ethics data protection requirements introduced for the research projects funded by the European Programme Horizon 2020. Initially, reference is made to the basic data protection principles introduced by the General Data Protection Regulation (GDPR) and the derogations permitted in the research field in favor of the science advancement. Although these derogations are subject to a number of safeguards to protect personal data, new ethics requirements are introduced for research projects funded by the European Programme Horizon 2020. The aim of these safeguards is the increased transparency and accountability at the data processing and the consequent enhanced protection of the individuals’ rights. These requirements are geared to the main research ethics postulate, which requires free, voluntary and informed participation of the research subject. Under these new requirements, Horizon 2020 beneficiaries/applicants must comply with a set of predefined standards, reflecting their ethical and legal obligations, provide a detailed and precise description of the technical and organisational measures that will be implemented in order to safeguard the rights of the research participants and also demonstrate their observance. In addition, depending on the type of the data being processed and the data processing techniques, the H2020 applicants/beneficiaries may need to provide a number of additional documents/explanations and implement further measures.